Atmospheric forcing as a source for ocean variability at the Brazil-Malvinas confluence zone - Simionato, Claudia Gloria (2001)
The goal of this study is to evaluate the impact of the atmospheric forcing of the scale of the storms on the oceanic circulation and temperature at the Brazil-Malvinas Confluence Zone. SST data and numerical simulations are used to get some insight on the mechanisms responsible for the establishment of the oceanic temperature and velocity fields response to the wind variability and to analyze the penetration depth, the time and the persistence of this response. Results show that atmospheric storms can be very effective on generating a SST persistent perturbation in the area and given their high frequency they can generate an important effect on the variability of the SST and its mean. Two possible mechanisms are considered for the oceanic response, the wind stress forcing and the heat exchange through the ocean-atmosphere interface. The latter probes to be the most important one. Even though the wind stress forcing has a rol on modifying the oceanic characteristics by means of advection, it is a slow process that will only be effective if the atmospheric perturbation remains for long periods. In contrast, the heat flux through the ocean surface is much more rapid and effective, particularly in cooling the ocean. The cooling of the ocean surface produces static instability and convection that rapidly transfers the cooling to lower layers. Vertical mixing relatively heats the ocean surface allowing for a new cooling by means of interaction with the atmosphere. Results show that even though most of the energy is lost as inertia-gravity waves, it takes to the ocean 24 hours to develop a geostrophically balanced response and it is proportional to the persistence of the atmospheric event. Once the response is setup into the ocean, it tends to remain even though the atmospheric disturbance disappears, because oceanic dissipative effects are of a much longer temporal scale than the atmospheric ones. The scale of penetration results to be of the order of 200 meters. Therefore, in a broad and shallow region such as the Argentinean continental shelf these events might be able to produce the mixing of the whole water column. Atmospheric storms in the area have a mean annual frequency higher than once a week and the signal is present in the ocean for a longer period. The results suggest that atmospheric variability on the scale of the storms can be very important on determining the local SST.